PENGARUH JENIS RIMPANG DAN KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN BIBIT JAHE MERAH (Zingiber officinale Rosc.) - Aidin, Anita; Sahiri, Nirwan; Madauna, Ichwan (AGROTEKBIS, 2016)
A Red ginger (Zingiber officinale Rosc.) is a herbal plant that is cultivated by farmers to meet the raw material of medicine industry and conserve the living environment. It contains various chemical substances such as essential oil and oleoresin (gingerol, zingeron, shogaol, and resin). It has a rhizome used to proliferation and hoarding food substances. Its rhizome can be devided into main rhizome and tillers rhizome. The main rhizome has an elliptical form while the tillers rhizome has a form of root which distend at the point and forming tubers. In cultivating red ginger, it needs the right media to support the growth. It is because the successful cultivation determined by the capability of plant production, therefore the use of right media is needed as the supplier of nutrients to get the optimal result for the growth of red ginger. This research was aimed to obtain the kinds of good rhizome and the right composition of planting media in breeding the red ginger. The significance of this research is to give informations about the kinds of good rhizome and the right composition of planting media in breeding red ginger. This research was conducted in an experimental design arranged based on a Randomized Block Design with two factors: first factor is the kind of rhizome consists of main rhizome and tillers rhizome; and second factor is the composition of planting media consist of: soil, soil + sand (1:1); soil + sand + chicken manure (1:1:1); soil + sand + straw (1:1:1). Therefore, there were 8 combination treatments and each treatment repeated for three (3) times. Every experimental unit has two (2) samples of plants. So, there are 48 samples of plants in the polybag. The result of this research shows that the treatment for rhizome type, the composition of planting media and the interaction has significant effect on the plant height, number of leaves, girth, number of shoots and leaf area on the plant agse of 4, 6, 8,10 and 12 weeks after planting (WAP). The highest plant height is 58.35 cm, the highest number of leaves is 13.83, the highest girth is 3.90 cm, the highest number of shoots is 5.67, and the highest leaf area is 418,27 cm2, by using the combination of tillers rhizome and the composition of soil planting media + sand + chicken manure with the composition ratio 1:1:1. Key Words: Planting media composition, Red Ginger, and rhizome.